DIFFERENTIAL ASSOCIATIONS OF MYOPIA WITH MAJOR AGE-RELATED EYE DISEASES : A SYSTEMATIC REVIEW - Valerie Gunawan, Alyssa Claudia; Caesari Putri, Aquirina; Atin, Fulgensius (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Myopia or nearsightedness is a refractive error caused by excessive axial elongation. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of cthe requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 63 articles, whereas the results of our search on SagePub brought up 21 articles. The results of the search conducted for the last year of 2013 yielded a total 44 articles for PubMed and 8 articles for SagePub. In the end, we compiled a total of  4 papers, 3 of which came from PubMed and 1 of which came from SagePub. We included five research that met the criteria. Conclusion: In summary, myopic eyes are less likely to have AMD and DR but more likely to have nuclear cataract, PSC, and POAG. The associations of myopia with AMD, DR, and POAG are mostly explained by longer AL. However, the association between myopia and nuclear cataract is explained by lens refraction rather than AL.